2000
DOI: 10.1146/annurev.immunol.18.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in T Cell Development and Function

Abstract: Glucocorticoids are small lipophilic compounds that mediate their many biological effects by binding an intracellular receptor (GR) that, in turn, translocates to the nucleus and directly or indirectly regulates gene transcription. Perhaps the most recognized biologic effect of glucocorticoids on peripheral T cells is immunosuppression, which is due to inhibition of expression of a wide variety of activationinduced gene products. Glucocorticoids have also been implicated in Th lineage development (favoring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
516
2
19

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 719 publications
(566 citation statements)
references
References 211 publications
(118 reference statements)
26
516
2
19
Order By: Relevance
“…We used dexamethasone since it is a well-studied hydrophobic drug with potent immunomodulating effects and has a K D with GR of B3 nM. 8,13 At the optimal in vitro formulation, at a charge ratio of 6:1 DS:DNA, each plasmid can deliver DS to a cell to result in about 30 nM final intracellular concentration of drug, well above the K D . Moreover, DS has anti-inflammatory activity in vivo and may be useful in its own right as a drug for inflammation, asthma, arthritis, or other inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used dexamethasone since it is a well-studied hydrophobic drug with potent immunomodulating effects and has a K D with GR of B3 nM. 8,13 At the optimal in vitro formulation, at a charge ratio of 6:1 DS:DNA, each plasmid can deliver DS to a cell to result in about 30 nM final intracellular concentration of drug, well above the K D . Moreover, DS has anti-inflammatory activity in vivo and may be useful in its own right as a drug for inflammation, asthma, arthritis, or other inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As soon as 5 min after the addition of DS/DOPE cells, GFP-GR fluorescence increased within the nucleus with complete localization occurring in less than 1 h similar to the localization induced by dexamethasone. Partial nuclear import of GFP-GR by 10 nM DS/DOPE and complete nuclear import at 100 nM suggested that the effective K D for DS was approximately 10-fold higher than that of dexamethasone (K D B3 nM), 13 potentially due to reduced access to the cytosolic GR caused by endosome sequestration or association of DS with anionic elements in the cytosol. While nuclear localization of GR is one test of glucocorticoid activity, we also employed a second test of pharmacological activity, the ability to induce gene expression from a glucocorticoidresponsive promoter.…”
Section: Pharmacological Activity Of Cationic Steroid In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Independently, the GR and the TCR induce apoptosis in T-hybridoma cells, yet together they promote T cell survival [24,25]. According to this so-called 'mutual antagonism' model, GC would, by preventing TCR-induced apoptosis, set the TCR avidity window for thymocyte selection [26]. This model predicts that any decrease in GR signaling leads to the deletion of thymocytes that would otherwise be positively selected.…”
Section: Introductionmentioning
confidence: 99%
“…7a. This particular pathway was of great interest because it represented regulation of the glucocorticoid pathway, and glucocorticoids are produced by thymic epithelial cells and it has been postulated that GR is necessary for thymocyte development [63]. Furthermore, as mentioned in the earlier section referring to CR prevention of ageassociated changes, we had also observed that the glucocorticoid receptor and HSPs display similar relationships but exhibit expression levels opposite from those seen in aging mice on an AL diet.…”
Section: Involvement Of the Glucocorticoid Receptor In The Aging Of Tmentioning
confidence: 52%